O menor abandonado e delinquente em Sergipe : da instrução ao cárcere (1942 - 1974) - Mendes, Alessandro Araújo (2014)
This dissertation was a research subject and the waif delinquent Sergipe period 1942-1974. It is a historical survey of bibliographical and documentary approach to the Cultural History. The overall goal was to analyze how the authorities dealt with the problem of homeless children and delinquent. The time frame is associated with the creation of the first public institution to host sergipana offenders and abandoned children, called the City of Minors Getúlio Vargas, which ran from 1942, the year of its inauguration in 1974, when it closed its doors after a crisis in the system welfare of minors. In the first section, i worked the representations of the lowest in the nineteen hundreds, the current legislation, the relationship of education, discipline and moral criminology child. In the second section, i presented the relationship of Social Assistance and the judiciary in the face of the problem smaller, the importance of education and education to work for the rehabilitation of the minor, the origin and the end of the Lower City of Sergipe; analysis of its resemblance to the models in which it was inspired , the problem of lower Sergipe, taking into account the judicial referrals: from education to prison, the House of Girls Santa Inês, as an institution to house abandoned girls in Sergipe and configuration of minors from legal proceedings; documents and newsletters individual judiciary, besides interviews with people who were part of the City of Minors Getúlio Vargas . Adopted as main concepts: "abandoned" (PEREIRA, 1994 and VEIGA and FARIA FILHO, 1999); "delinquent" (RIZZINI, 1995 and VEIGA and FARIA FILHO, 1999),"education" (DURKHEIM, 1978 and JINZENJI, 2010); statement (JINZENJI, 2010) and "minor" (RIZZINI, 2010; PERES, 2002 and VEIGA and FARIA FILHO, 1999). So with this research, i intend to contribute to the historiography sergipana about the history of education of homeless children and delinquent in Sergipe.